AL001 restores CSF PGRN levels and normalizes disease‐associated biomarkers in individuals with frontotemporal dementia due to heterozygous mutations in the progranulin gene: Human: Putative therapeutic results for Alzheimer's and related dementias. (7th December 2020) - Haynes, Beth Ann; Rhinn, Herve; Yeh, Felix L; Long, Hua; Ward, Michael; Hagey, Mackenzie; Siddiqui, Omer; Paul, Robert
Abstract: Background: AL001 is a recombinant humanized anti‐Sortilin monoclonal antibody in development for frontotemporal dementia (FTD). Mutations in a single copy of the progranulin gene (GRN) leads to a 50% or greater decrease in the level of circulating progranulin (PGRN) protein levels and are causative of FTD. The disease is associated with increased inflammation and impaired lysosomal function in the brain. The INFRONT Phase 1/1b clinical study AL001‐1 investigated the safety, tolerability, pharmacokinetics and pharmacodynamics of intravenously administered AL001 in healthy volunteers (HV) and participants with a GRN mutation causative of FTD (FTD‐GRN). In addition, the study investigated the effect of AL001 on disease‐associated biomarkers. Method: A total of 64 participants were enrolled in the AL001‐1 study. In the single dose ascending part of the study, 50 healthy volunteer participants were enrolled with 38 exposed to AL001 and 12 exposed to placebo. The study enrolled 6 asymptomatic FTD‐GRN and 8 symptomatic FTD‐GRN participants. The 8 symptomatic FTD‐GRN participants received 3 doses of 30 mg/kg of AL001 over 4 weeks. Result: Treatment of symptomatic FTD‐GRN participants with AL001 over 4 weeks restored PGRN levels in the cerebrospinal fluid (CSF) to normal levels for more than 8 weeks. To further investigate the effects of restoring PGRN levels, partial normalization of a FTD disease proteomic signature was observed in the CSF 4 weeks after the last dose in multidose treatment group. Compared to healthy volunteers, AL001 treatment rescued cathepsin B (CTSB), a marker of lysosomal function, by 58%. AL001 treatment also partially normalized markers of inflammation and gliosis, osteopontin (SPP1) and chitotriosidase (CHIT1) by 52% and 22%, respectively. In addition to the reversal of these disease phenotypes, a 14% reduction (n.s.) in plasma neurofilament light chain (NfL), a marker of neuron injury and stress, was observed after 8 weeks after the last dose. Conclusion: AL001 treatment resulted in a sustained increase in plasma and CSF PGRN in FTD‐GRN mutation carriers. New data showed reduction of NfL and normalization of proteins associated with the disease after one month of dosing. These results have supported progressing AL001 to Phase 2 and pivotal Phase 3 studies.